Tax and Accounting Treatment on the Revaluation of Fixed Assets (Land) in Indonesia - Mila Austria Reyes; Gita Ghaisani Haniyah (JAAF (Journal of Applied Accounting and Finance), 2020)
Revaluation of assets Property, Plant and Eguipment (PPE)  is carried out by a company with the aimed to provide financial statements  which are more fair and reasonable. However, the question arise about how is the tax treatment for this asset assessment. The lack of regulations that regulate it makes the author to be motivated to  research and hopefully can provide information to taxpayers and give suggestions to the tax authorities regarding how the tax treatment for this asset assessment. This research is using a qualitative approach with data collection through in-depth interview and literature study. The research conclude to eliminate all of the perception regarding the actual tax treatment, the tax regulator must always update or revise the tax regulations with changes or revisions made by the Financial Accounting Standards (SAK). This research is limited  only on the discussion of the tax treatment towards revaluation based on the Statement of Financial Accounting Standards (PSAK) 16.